The Influence of Wind Direction and Speed on Rainfall in Bengkulu City (2019-2023) Based on the Schmidt-Fergusson and Wind Rose Models - Agustin, Rika Amelia; Ekawita, Riska; Supiyati, Supiyati; Alfando, Andre (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Increasingly extreme climate change has increased rainfall intensity and uncertainty of weather patterns in many parts of Indonesia, including Bengkulu City. This phenomenon affects rainfall patterns, the duration of the wet and dry seasons, and wind speed, all of which have an impact on various aspects of life. This study analyzes the effect of wind direction and speed on rainfall in Bengkulu City using the Schmidt-Fergusson, Wind Rose, and Multiple Linear Regression models, based on data from the Fatmawati Soekarno Bengkulu Meteorological Station in 2019-2023. The results of this study indicate that the dominant wind direction comes from the north, northeast, and southeast, with an average speed of 2.47 m/s, categorized as a weak wind according to the Beaufort scale. The highest annual rainfall was recorded in October 2022 at 600 mm. Based on the Schmidt-Fergusson classification, Bengkulu City is included in climate type A with a Q value = 0.1. Regression analysis shows that wind speed has a significant negative effect on rainfall indicating that wind speed has a negative effect, meaning that an increase in wind speed will cause a decrease in rainfall, while humidity has a positive effect, indicating that when air humidity increases, rainfall will also increase. The R² value of 32.7% indicates that the wind, temperature, pressure, and humidity variables explain some of the variation in rainfall. This finding emphasizes the importance of monitoring wind elements in the early warning system for extreme weather and supports hydrometeorological disaster risk mitigation planning in coastal areas vulnerable to climate change.